Pengaruh Pendidikan Kewirausahaan dan Lingkungan Sekolah terhadap Minat Berwirausaha Siswa SMK di Jakarta Selatan - Desfi Dwiyana Nurhayati; Corry Yohana; Aditya Pratama (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This study aims to determine the effect of entrepreneurship education and the school environment on the entrepreneurial interest of Vocational High School (SMK) students in South Jakarta. The background of this study is based on the importance of developing an entrepreneurial spirit among the younger generation as a strategic effort in facing employment challenges and encouraging the creation of new jobs. SMK students are seen as potential entrepreneurs who need to be equipped with entrepreneurial knowledge, skills, and attitudes from an early age. Therefore, entrepreneurship education and the school environment are two crucial factors that can shape entrepreneurial mindsets and motivations. This study uses a quantitative approach with an associative research type. The study population was students from five vocational high schools spread across South Jakarta. A sample of 173 respondents was selected through a stratified random sampling technique based on school strata and gender to obtain representative data. Data were collected using a closed questionnaire instrument that has been tested for validity and reliability. The data analysis technique used was multiple linear regression, which began with classical assumption tests such as normality, multicollinearity, heteroscedasticity, and linearity. The results of the study indicate that partially, entrepreneurship education has a positive and significant influence on students' entrepreneurial interest. Similarly, the school environment also has a positive and significant influence. Simultaneously, both variables contribute to increasing entrepreneurial interest, with an Adjusted R Square value of 0.412. This means that 41.2% of the variation in entrepreneurial interest can be explained by entrepreneurship education and the school environment, while 58.8% is influenced by other factors. These findings emphasize the important role of schools in creating a learning ecosystem that encourages innovation, independence, and an entrepreneurial spirit among students.